Identity interplay: The importance and challenges of consumer research on multiple identities. Issue 1 (19th January 2021) - Forehand, Mark; Reed, Americus; Saint Clair, Julian K.
Abstract: Although it is well accepted that the self‐concept includes numerous identities, the preponderance of past consumer identity research has explored one identity at a time and this focus has limited new insights into the interplay between identities. We integrate across research streams to propose a Multiple‐Identity Network as a unifying framework to help inform and direct future research on multiple identities. This framework identifies three important areas of opportunity for research on multiple identities: (a) Identity Structure, (b) Identity Management, and (c) Identity Change processes that drive both structure and management.